The latitude-dependent autoimmune disease risk genes ZMIZ1 and IRF8 regulate mononuclear phagocytic cell differentiation in response to vitamin D. (4th October 2018) - Parnell, Grant P; Schibeci, Stephen D; Fewings, Nicole L; Afrasiabi, Ali; Law, Samantha P L; Samaranayake, Shanuka; Kh'ng, Jing Hui; Fong, Yee Hsu; Brown, David A; Liddle, Christopher; Stewart, Graeme J; Booth, David R
Abstract: Epidemiological, molecular and genetic studies have indicated that high serum vitamin D levels are associated with lower risk of several autoimmune diseases. The vitamin D receptor (VDR) binding sites in monocytes and dendritic cells (DCs) are more common in risk genes for diseases with latitude dependence than in risk genes for other diseases. The transcription factor genes Zinc finger MIZ domain-containing protein 1 (ZMIZ1) and interferon regulatory factor 8 (IRF8)—risk genes for many of these diseases—have VDR binding peaks co-incident with the risk single nucleotide polymorphisms (SNPs). We show these genes are responsive to vitamin D: ZMIZ1 expression increased and IRF8 expression decreased, and this response was affected by genotype in different cell subsets. The IL10/IL12 ratio in tolerogenic DCs increased with vitamin D. These data indicate that vitamin D regulation of ZMIZ1 and IRF8 in DCs and monocytes contribute to latitude-dependent autoimmune disease risk.